Age-specific prevalence of HPV genotypes in cervical cytology samples with equivocal or low-grade lesions - Brismar-Wendel, S (Nature Publishing Group, 2009)
BACKGROUND: To define the spectrum of human papillomavirus (HPV) types and establish an age limit for triage HPV testing in atypical squamous cells of undetermined significance (ASCUS) and low-grade squamous intraepithelial lesion (LSIL). MATERIALS AND METHODS: 343 liquid-based cytological samples from the population-based screening programme with minor abnormalities were subjected to HPV genotyping (Linear Array, Roche, Basel, Switzerland). RESULTS: High-risk human papillomavirus (HR-HPV) was found in 71% of LSIL and 49% of ASCUS cases (P<0.001). High-risk human papillomavirus prevalence was age-dependent in LSIL (P=0.01), with decreasing prevalence until the age of 50 years, followed by a slight increase. Human papillomavirus type 16 was the most common HR-HPV, found in 23% of HPV-positive women. Human papillomavirus type 18 was the sixth most common, found in 9.9% (P<0.001). An age-dependent quadratic trend was observed for multiple infections (P=0.01) with a trough at about 42 years. The most common HR-HPV types to show a coinfection with HPV16 (clade 9) were HPV39 (28%), 45 (38%), and 59 (46%), belonging to HPV18 clade 7. The frequency of low-risk (LR) vs probable HR and HR-HPV also followed an age-dependent quadratic trend. CONCLUSIONS: After the age of 25 years, HR-HPV prevalence is similar in LSIL and ASCUS cases, motivating a low age limit for triage HPV testing. Multiple infections and LR/HR-HPV dominance are age-dependent. Genotyping in longitudinal design is needed to elucidate the importance of multiple infections in cancer progression and in cross-protection from vaccination.